Inclusion and teachers’ attitudes towards students with Autism Spectrum Disorder: reflections from a pilot study - Aiello, Paola; Di Gennaro, Diana Carmela; Girelli, Laura; Olley, John Gregory (Formazione & insegnamento, 2018)
In recent years, international educational policies and documents have outlined a new profile of teacher competencies, highlighting the need to start from their personal sphere to build the professional dimension in an inclusive direction. In this regard, a construct on which the research has focused attention is that of attitudes as a variable that influences the success of inclusion processes especially in the presence of students with complex disorders such as those of the autistic spectrum, assuming that the presence of a deficit in the area of social interaction makes social participation very difficult to achieve. In the wake of these considerations, the present study is aimed at the validation of the Autism Attitude Scale for Teachers (AAST, Olley et alii, 1981) as a means of assessing teachers’ attitudes toward students with autism spectrum disorder, outlining its possible utility for future research aimed at analyzing one of the supporting dimensions of the concept of inclusive competence.